The variability of maximum vertical jumps - Yoon, Suk Hoon; Challis, J. H. (Journal of Human Movement Studies, 2005)
The purpose of this study was to examine the variability of the time profiles of the kinematics and kinetics of a series of maximum vertical jumps. Ten male subjects (height 1.77m±0.058; body rnass 73.4kg±8.5; age 25.3yrs±3.0) each performed ten maximum countermovement vertical jumps. Kinematic and kinetic data were collected and the coefficients of Variation (CV) for the intra- and inter-subject data computed for the ground reaction force profiles, and hip, knee, and ankle angles, angular velocities and resultant joint moment profiles. The mean CV for the subjects in jump height was 5. l %±2.7. The intra-subject CVs for the resultant joint moments were 14.8%±2.3, 12.7%±1.9, 20.6%±4.3 for the ankle, knee and hip joints respectively. For the inter-subject data the CVs were 28.1%, 25.7%, and 36.9%. In comparison to data in the literature for walking and slow running, the variability of the kinematics and kinetics were much lower for maximal jumping. The study provides guidance for design of studies of jumping, äs it demonstrates that low variability justifies selecting a single trial from a sequence for subsequent analysis.